Physicochemical Properties of Cetrimonium Bromide in Electrolytes and Nonelectrolyte Environments - Joshi, Riddhi H.; Dave, Nikunj N.; Joshi, Tejas P. (Current Physical Chemistry, 2024)
Background: The physicochemical properties, including the thermodynamics of micellization studies, received much attention. Cationic surfactant cetrimonium bromide (C16TABr) in electrolytes (sodium chloride and sodium salicylate) and nonelectrolyte (Ethylene glycol) in an aqueous solution were examined, and interesting results were obtained. The present investigation aims to identify a suitable combination of cationic surfactant cetrimonium bromide + electrolytes and nonelectrolytes having the ability to alter the size or shape of the micellar system using available methods. Methods: Surface tension, conductivity, viscosity, ultrasonic velocity, and dynamic light scattering (DLS) methods at different temperatures (303-323K) were used during the experimental research work. Results: The experimental results pointed out that the incorporation of electrolytes and nonelectrolyte into the cationic surfactant affects the physicochemical properties such as critical micelle concentration (CMC), surface tension (ST), degree of ionization (α), degree of counterion binding (β), standard Gibbs free energy of micellization (ΔGom), standard entropy of micellization (ΔSom), standard heat of micellization (ΔHo m), viscosities, and acoustic parameters. Dynamic light scattering (DLS) measurements reveal exciting facts related to the size and shape transformation of the mixed micellar assembly. Structure modification can be obtained by choosing right the combination of cationic surfactant cetrimonium bromide + electrolytes (sodium chloride and sodium salicylate) and nonelectrolyte (Ethylene glycol) ratio. Conclusion: It concluded that, over a threshold level, an electrolyte such as NaCl concentration causes the micelle size to rise. The entropy of micellization goes down when a structure-breaker (EG) is added to the water phase, and this is because the structure of the water is changed near hydrophobic groups. The physicochemical features of cetrimonium bromide (C16TABr) show unique behaviour under the influence of micelle-driven and micelle- forbidden systems.
Keywords: dynamic light scattering